Process-Specialized Technologies Using in Agricultural Robotics - I. V. Rubtsov; O. G. Rusanova; Z. A. Godzhaev (Сельскохозяйственные машины и технологии, 2018)
The article presents the main results of the analysis of the agriculture automation level in Russia and in the world. The results of the research of the foreign market, structures and compositions of foreign-made unmanned mobile energy vehicles are presented. The main direction of development of foreign companies is the creation of new models of navigation and orientation equipment for agricultural machinery aimed to the implementation of autonomous moving and mission equipment control. Technics automatization is possible due to refitting of already existing samples with specialized attachments. According to this analysis, foreign agricultural machinery is far ahead of domestic manufacturers for the production of crew-unmanned facilities of mechanization for the agricultural sector, and the material intensity of the existing agricultural production in Russia is 3-4 times higher than that of foreign countries. The need for this kind of analysis is explained by the result of a comparison labor productivity: this index in Russia's agriculture is by 2.4 times lower than European one and 3.5 times lower than that of the USA. The Russian agriculture development retard can be eliminate through the use of modern achievements in the field of robotic systems for special purposes. The authors proved the possibility of double use of technologies because of similarity of schemes and structure of robotic systems for the solution of specialized tasks of both directions. The unmanned mobile energy vehicles can be used at sequential and parallel autonomous driving.